Warm conveyor belts in present-day and future climate simulations - Part 1: Climatology and impacts - Joos, Hanna; Sprenger, Michael; Binder, Hanin; Beyerle, Urs; id_orcid:0 000-0002-6464-0838; Wernli, Heini; id_orcid:0 000-0001-9674-4837 (Copernicus, 2023)
This study investigates how warm conveyor belts (WCBs) will change in a future climate. WCBs are strongly ascending airstreams in extratropical cyclones that are responsible for most of their precipitation. In conjunction with the cloud formation, latent heat is released, which has an impact on the potential vorticity distribution and therefore on the atmospheric circulation in the middle and upper troposphere. Because of these and other impacts of WCBs, it is of great importance to investigate changes in their frequencies, regions of occurrence, and physical characteristics in a warmer climate. To this aim, future climate simulations (Representative Concentration Pathway 8.5 - RCP8.5 - scenario; 2091-2100) are performed with the Community Earth System Model version 1 (CESM1) and compared to present-day climate (1991-1999). Trajectories are calculated based on 6-hourly 3D wind fields, and WCBs are identified as trajectories that ascend at least 600 hPa in 2 d. WCBs are represented reasonably well in terms of location and occurrence frequency compared to WCBs in the ERA-Interim reanalyses. In a future climate, WCB inflow regions in the North Pacific are systematically shifted northward in winter, which is in agreement with the northward shift of the storm track in this region. In the North Atlantic, increased frequencies are discernible in the southwest and there is a decrease to the south of Iceland. Finally, in the Southern Hemisphere, WCB frequencies increase in the South Atlantic in both seasons and to the east of South Africa and the Indian Ocean in June-July-August (JJA). These changes are partly consistent with corresponding changes in the occurrence frequencies of extratropical cyclones, i.e. the driving weather systems of WCBs. Changes are also found in the WCB characteristics, which have implications for WCB impacts in a future climate. The increase in inflow moisture in the different regions and seasons - ∼23 %-33 % (∼14 %-20 %) in winter (summer) - leads to (i) an increase in WCB-related precipitation ...